Emergence of oxacillinase-181 carbapenemase-producing diarrheagenic Escherichia coli in Ghana - Prah, I.; Ayibieke, A.; Mahazu, S.; Sassa, C.T.; Hayashi, T.; Yamaoka, S.; Suzuki, T.; Iwanaga, S.; Ablordey, A.; Saito, R. (Taylor & Francis Group, 2021)
The emergence and spread of carbapenemase-producing bacteria are serious threats to public health. We characterized two OXA-181-producing Escherichia coli isolates from pediatric patients with diarrhea from Ghana. blaOXA-181 was localized on the self-conjugative IncX3-containing plasmid in the E. coli ST410 isolate, belonging to an emerging lineage, and an IncFIC(FII)-containing plasmid in E. coli ST940. The blaOXA-181-qnrS1 region was found on the IS26 composite transposon, which contained a 366-bp deletion in the region encoding the Rep A protein for the IncX3- containing plasmid. The IncFIC(FII) plasmid was novel and integrated with an approximately 39-kb IncX1 plasmid through conjugal transfer. Both plasmids clustered close to plasmids from Switzerland. To the best of our knowledge, this is the first report describing the presence of an IncX3 plasmid containing blaOXA-181 in strains closely related to the B4/H24RxC clade in Africa, suggesting its emergence and the need to strengthen antimicrobial resistance surveillance.
Research Article
Keywords: ST410; oxacillinase-181; diarrheagenic E. coli; IncX3; IncFIC(FII); B4/H24RxC clade